Factors that affect the English language teaching - learning process in Ecuadorian public high schools, estudio realizado en los colegios 17 de Julio, Victor Manuel Guzmán, Colegio de Señoritas Ibarra, Abelardo Moncayo, Teodoro Gómez y Municipal de la provincia de Imbabura, en el año lectivo 2012 - 2013 - Castro Guzmán, Janet del Pilar (2013)
The purpose of the research was to analyze factors that affect the English language teaching - process in Ecuadorian public high schools. The method used was quantitative. This investigation was carried out in six Ecuadorian public high schools in Imbabura in 2012. The sample consisted of 15 teachers from 8th basic education to 3rd year of senior high school. The information was gathered through surveys, interviews, and observations. In this research, it was necessary to observe fifteen classes in order to determine factors concerning teachers, students, classrooms, and educational institutions. Moreover, the research process involved interviewing and surveying fifteen EFL teachers. After finishing each observed lesson, fifteen students were also surveyed. At the end of the research, it was found that factors affecting the English teaching -learning process in Ecuadorian public high schools include the large number of students in the classroom, the lack of a variety in the teaching methods, the lack of supervision of EFL classes, among other factors.